Molecular typing of fecal eukaryotic microbiota of human infants and their respective mothers - Pandey, Prashant K; Siddharth, Jay; Verma, Pankaj; Bavdekar, Ashish; Patole, Milind S; Shouche, Yogesh S (Journal of biosciences, 2012)
The micro-eukaryotic diversity from the human gut was investigated using universal primers directed towards 18S rRNA gene, fecal samples being the source of DNA. The subjects in this study included two breast-fed and two formula-milk-fed infants and their mothers. The study revealed that the infants did not seem to harbour any micro-eukaryotes in their gut. In contrast, there were distinct eukaryotic microbiota present in the mothers. The investigation is the first of its kind in the comparative study of the human feces to reveal the presence of micro-eukaryotic diversity variance in infants and adults from the Indian subcontinent. The micro-eukaryotes encountered during the investigation include known gut colonizers like Blastocystis and some fungi species. Some of these micro-eukaryotes have been speculated to be involved in clinical manifestations of various diseases. The study is an attempt to highlight the importance of micro-eukaryotes in the human gut.